The Effect Of Casgot Property On The Biological Properties Of Soil In Which Cucumbers Are Planted - Ryan Agfandri, Dwi; Walida, Hilwa; Elizabeth Mustamu, Novilda; Ainy Dalimunthe, Badrul (International Journal of Science, Technology & Management, 2024)
Soil biological properties are various aspects related to the life of microorganisms and macroorganisms in the soil and biological activities. This study aims to understand how soil organisms and their biological activities contribute to soil fertility and plant health. This study used a purposive sampling method and was analyzed using descriptive analysis. Soil biological properties, including the total number of bacteria and fungi, were observed to assess the effect of Black Soldier Fly larvae (kasgot) fertilizer application. The results showed that treatment variations had a significant effect on the population of fungi and bacteria in the rhizosphere. The highest value of the fungal population was recorded in the M1 treatment without the first treatment, while the lowest value was in the M1 treatment with the first treatment, indicating that the type and frequency of treatment can drastically affect fungal growth. For the bacterial population, the M3 treatment in the first application showed the highest effectiveness, while the M2 treatment in the second application showed the lowest results, highlighting the importance of the dose and application stage in increasing the bacterial population. Overall, this study emphasizes the importance of selecting the right treatment to optimize the soil microbial population in agricultural practices.